Effect of micro-magnesium oxide admixture on rheological and compressive strength properties of class G well cement - Chen, Weiqing; Mahmoud, Ahmed Abdulhamid; Elkatatny, Salaheldin (Frontiers in Materials, 2022)
Rheological property tuning is one key aspect of oil-well cement, not only affecting the cement slurry placement but also indirectly impacting other cementing properties such as the bonding strength and compressive strength. However, the research is scant on the rheological properties of blending magnesium oxide with class G oil-well cement, despite some studies having been conducted on its impacts on shrinkage compensation, compressive strength, bonding strength, and permeability properties of oil-well cement. This work studies the effects of micro-sized magnesium oxide on the rheological properties and compressive strength of the formulated API Class G oil-well cement slurries. Two types of micro-sized magnesium oxide (50 μm and 100 μm) were used as the mineral admixture at different dosages (3%, 9%). The base formulated slurry sample was incorporated with the silica flour and several commercialized additives such as retarder, fluid loss control agent, and defoamer. A batch of flow tests have been conducted by the use of a digital viscometer at two different temperatures, 25 and 88°C. The compressive strength has also been measured after curing the samples with the same formulation and conditions for 7 days. The variations of the rheological properties (plastic viscosity, yield stress, and gel strength), shear stress–shear rate correlations, and shear-thinning/thickening behavior are impacted by the temperature, the type, and dosage of magnesium oxide. The plastic viscosity of the tested slurries decreased by 27.0% (type II, 9%, 25°C) and 15.1% (type II, 3%, 88°C), respectively, and the yield stress increased by 258.5% (type II, 3%, 88°C) and 53.9% (type II, 9%, 25°C). The gel strength generally increases as the magnesium oxide dosage increases. However, all tested slurry samples show shear-thinning behavior and non-Newtonian characteristics. Among the tested slurry samples, it is found that better rheological performance is achieved when incorporating magnesium oxide with a smaller particle size. On the other side, the specimens of mixed magnesium oxide with a bigger particle size and medium dosage outperform their rival with a smaller particle size in compressive strength.